Adaptive DNA computing algorithm by using PCR and restriction enzyme - Watanabe, Shinpei; Tsuboi, Yusei; Ibrahim, Zuwairie; Yamamoto, Tsuneto; Ono, Osamu (IEEE, 2004)
In this paper, we introduce a new adaptive DNA coinpitting algorithm by using Poiymcruse Chain Rearlion (PCR). The adaptive algorithm is designed based on Adleman-Lipton [3I paradigm of DNA computing, However, unlike the Adleman- Lipton architecture, a cutting operation has been introduced to the algorithm and the mechanism in which the molecules used by computation were feedback to the next cyclc was devised. Morcovcr, amplification by PCR is performed in the molecule used by feedback and a concentration difference arises in the base sequence can be used again. By doing this, the molecules which serve as a solution candidate can he narrowcd down and the optimal solution can be detected easily. From the application point of view, a simulation has been carried out on the shortest puth problem and the validity of the proposed adaptive algorithm is stated from the results of the simulation. Finally, we go on to propose applying adaptive algorithm to the chemistry experiment which used the actual DNA molecules for soiving B universal problem.